Mende Parametric Electric Generator (Global Journal of Science Frontier Research, 2018)
From an energy point of view its transfer on the direct current is the most advantageous method of the transfer of the large volumes of electric power up to the great distances. However, up to now there does not exist such direct-current generators, which are capable of generating the necessary level of power with the lumped voltages. In this article this problem is solved. The law of capacitive parametric induction is assumed as the basis of the solution of problem.
Keywords: current; voltage; capacity; capacitive parametric induction; direct-current generator; the transformer of constant voltage; water pump